School as a Childhood Place. Experience of 3rd-Grade Elementary School Students - Barbara Lulek (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: Childhood is a very important stage in life, during which a child defines itself and its life undertaking numerous activities, initially in the family environment and later in school. School is one area of children's existence in which everyday life concentrates for many years. The article presents images of childhood spent in school, referring to occupied places and undertaken activities. Research Aim:The study's aim was to learn about the experience of 3rd-grade students connected to school as a childhood place. Method: The research was carried out in the paradigm of qualitative research, constructed on narrative interviews. Researchers used friendly methods of collecting data when examining children. The respondents created artworks which became reference introductions to the interview. The 3rd-grade students described their school's reality and experience. Results: Coded empirical data enabled to identify categories depicting school as a childhood place. Taking into account security, attractiveness, activity and identity, they were named as follows: school as a place for children's games, school as a place to learn with others, school as a place of building identity and school as an untamed place. Conclusions: Research shows that school is a place where the personal treatment of a child is not always dominant in terms of an active self-regulatory person. For some children this is an area related to experiencing their own lonely individuality.